2011
DOI: 10.1179/147842209x12579401586528
|View full text |Cite
|
Sign up to set email alerts
|

Study of molybdate–phytic acid passivation on galvanised steel

Abstract: A combined molybdate-phytic acid passivation treatment on galvanised steel is studied in this paper. Both copper decoration drop tests and immersion mass loss tests indicated that the combined molybdate-phytic acid passivated samples showed better corrosion resistance than that of samples treated separately by molybdate or phytic acid. The electrochemical behaviours of the passivated samples were investigated using potentiodynamic polarisation and electrochemical impendence spectra in 0?5 mol L 21 NaCl solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Later the same authors [70] using the dropping and immersion mass loss tests found that samples passivated with a combined molybdate-PhA solution (20 g/l Na 2 MO 4 ; 20 g/l PhA; 1 g/l NaNO 2 ; 3 ml/l 63% HNO 3 ; 0.2 ml/l 98% H 2 SO 4 ) showed better corrosion resistance than samples treated separately by molybdate or PhA. The electrochemical behaviour of the passivated samples was studied using potentiodynamic polarization and EIS in 0.5 M NaCl solution and showed i cor = 4.95·10 -5 ; 5.10·10 -5 and 1.19·10 -5 A·cm -2 , respectively.…”
Section: Organic Esters Of Phosphoric Acidmentioning
confidence: 92%
“…Later the same authors [70] using the dropping and immersion mass loss tests found that samples passivated with a combined molybdate-PhA solution (20 g/l Na 2 MO 4 ; 20 g/l PhA; 1 g/l NaNO 2 ; 3 ml/l 63% HNO 3 ; 0.2 ml/l 98% H 2 SO 4 ) showed better corrosion resistance than samples treated separately by molybdate or PhA. The electrochemical behaviour of the passivated samples was studied using potentiodynamic polarization and EIS in 0.5 M NaCl solution and showed i cor = 4.95·10 -5 ; 5.10·10 -5 and 1.19·10 -5 A·cm -2 , respectively.…”
Section: Organic Esters Of Phosphoric Acidmentioning
confidence: 92%
“…The inhibiting effect of phytic acid, its salts and formulations based thereon was observed not only to the above metals, but also to galvanized steel [120]. For example, in [121] a method was suggested for the passivation of galvanized steel in a molybdatephytate solution (20.0 g/L Na 2 MO 4 , 20.0 g/L phytic acid, 1.0 g/L NaNO 2 , 3.0 mL/L 63% HNO 3 , 0.2 mL/L 98% H 2 SO 4 ). According to the results of the droplet and immersion mass loss tests, the films obtained in this solution increased the corrosion resistance of galvanized steel better than those obtained in solutions of molybdate or phytic acid alone.…”
Section: Organophosphates 221 Organic Esters Of Phosphoric Acidmentioning
confidence: 99%
“…Uma revisão na literatura sobre o pré-tratamento de conversão de superfícies de aço carbono 1020 com HP na promoção de adesão e proteção à corrosão de revestimentos poliméricos como a PAni e POMA às superfícies metálicas, é quase inexistente. Contudo, vários trabalhos científicos foram encontrados relativos à pré-tratamento de conversão com ácido fítico, à maioria se refere ao ferro [50,51], cobre [52], ligas de alumínio [53,54], metal magnésio e ligas de magnésio [55][56][57][58][59][60][61][62][63][64][65], metal níquel [66] e aços galvanizados [67,68] cuja revisão permitiu desenvolver uma base de estudo para a otimização de parâmetros de pré-tratamento e póstratamento de superfícies para o aço carbono AISI 1020 com ácido fítico e sais de cério e posterior aplicação de coberturas poliméricas e avaliação contra a corrosão.…”
Section: Camadas De Conversão De áCido Fíticounclassified
“…Foram usadas técnicas eletroquímicas, polarização potenciodinâmica, espectroscopia de impedância eletroquímica em solução NaCl 0,5 mol/L para avaliar a resistência à corrosão. Os resultados mostraram que a camada de conversão de Ce/HP apresenta maior resistência à corrosão devido ao efeito sinérgico entre o cério e o ácido fítico.Íons de cério e ácido fítico podem formar quelatos que conduz a passivação ao aço galvanizado.Em outro trabalho, Liu et al[68] investigaram camadas de conversão de HP, molibdato e Mo/HP formadas também no substrato do aço galvânico. Os autores concluíram que a camada de conversão de Mo/HP é mais compacta e oferece maior resistência à corrosão comparada a dos aços tratados com molibdato e HP isoladamente.…”
unclassified